Half-Elemental Diet Shifts the Human Intestinal Bacterial Compositions and Metabolites: A Pilot Study with Healthy Individuals - Jun Miyoshi; Daisuke Saito; Mio Nakamura; Miki Miura; Tatsuya Mitsui; Toru Kudo; Shinnosuke Murakami; Minoru Matsuura; Tadakazu Hisamatsu (Gastroenterology Research and Practice)
Background and Aim. Half-elemental diet (ED) (900 kcal/day of ED) has clinical efficacy to treat Crohn’s disease (CD). However, the underlying mechanisms of how the ED exerts its efficacy remain unclear. Alterations of the gut microbiota, known as dysbiosis, have been reported to play a role in CD pathogenesis. Many variables including diet affect the gut microbiota. We hypothesized that half-ED has the potential to change the gut microbiota composition and functions leading to anti-inflammatory actions. Given that inflammation can be a confounding factor affecting the intestinal microbiota, we aimed to test our hypothesis among healthy individuals in this pilot study. Methods. This prospective study included four healthy volunteers. The subjects continued their dietary habits for 2 weeks after the registration of the study and then started half-ED replacing 900 kcal of the regular diet with ED (time point 1, T1). The subjects continued half-ED for 2 weeks (T2). After the withdrawal of ED, subjects resumed their original dietary habits for 2 weeks (T3). Fecal samples were collected from all subjects at all time points, T1-3. Fecal DNA and metabolites were extracted from the samples. We performed 16S rRNA gene amplicon sequencing and metabolomic analysis to examine the bacterial compositions and intestinal metabolites. Results. There were differences in the gut bacterial compositions and metabolites at each time point as well as overtime changing patterns between subjects. Several bacteria and metabolites including short-chain fatty acids and bile acids altered significantly across the subjects. The bacterial membership and intestinal metabolites at T3 were different from T1 in all subjects. Conclusions. Half-ED shifts the gut bacterial compositions and metabolites. The changes varied with each individual, while some microbes and metabolites change commonly across individuals. The impact of half-ED may persist even after the withdrawal. This trial is registered with UMIN ID: 000031920.